Adaptive capacity and potential properties of varieties bred at the Potato Research Institute of NAAS - А. Ф. Борівський (Plant Varieties Studying and Protection)
Purpose. To establish adaptive capacity and reproduction time of the registered potato varieties elite bred at the Potato Research Institute of NAAS of Ukraine in various edaphic and climatic zones of Ukraine. Methods. Field and laboratory tests, statistical evaluation. Results. Potato varieties were tested in the Forest-Seppe, Polissia and Steppe zones of Ukraine. Over the years of testing (2012–2014), the highest yield of potatoes in the south-western part of the Forest-Steppe zone was produced by the early varieties: ‘Kimmeria’ – 46.9 t/ha, ‘Vedruska’ – 38.6 t/ha; middle-early varieties: ‘Partner’ – 33.2 t/ha, ‘Fantazia – 27.7 t/ha; mid-season varieties: ‘Okolytsia’ – 35.4 t/ha, ‘Mandrivnytsia’ – 25.1 t/ha. In the Central Polissia, ‘Kimmeria’ (31 t/ha) was the most productive early variety, the yield at the level of 27.6–29.2 t/ha was formed by such varieties as ‘Skarbnytsia’, ‘Serpanok’, ‘Radynka’, ‘Tyras’. Among the middle-early varieties, the yield of 33.1 t/ha was obtained from the variety ‘Partner’. In the conditions of Steppe zone, such early potato varieties as ‘Vymir’, ‘Glazurna’, ‘Strumok’, ‘Kimmeria’, ‘Svitoch’ and the middle-early variety ‘Ariya’ had the highest productivity in case of growing as bivoltine crop under irrigated conditions. It was found that in the Forest-Steppe and Polissia zones such varieties as ‘Kimmeria’, ‘Vedruska, ‘Serpanok’, ‘Skarbnytsia, ‘Tyras’, ‘Radynka’, ‘Partner’, ‘Slovianka’, ‘Vernisazh’, ‘Mandrivnytsia’, ‘Poliske dzherelo’ and ‘Chervona ruta’ were characterized by high resistance to degeneration (viral diseases and loss of productivity of potato elite in the process of reproduction). According to the results of evaluation of the impact of elite potato reproduction time on affection by viral diseases, optimal time for elite renovation for investigated varieties was determined. Conclusions. In the process of testing in various edaphic and climatic zones of Ukraine, stable yield with a high seed tubers number, regardless of weather conditions during the growing season in the Forest-Steppe and Polissia zones, was formed by some early potato varieties (‘Kimmeria’, ‘Vedruska’, ‘Radynka) and middle-early one (‘Partner’). Among mid-season varieties ‘Vernisazh’, ‘Okolytsia’, ‘Mandrivnytsia’ were identified for high productivity, and among middle-late – ‘Poliske dzherelo’ and ‘Chervona ruta’. The most common viral diseases of potatoes were rugose mosaic and mosaic leaf curling. High efficiency of the use of bivoltine crop method for potato growing to obtain seed material in the Southern Steppe zone of Ukraine has been proved.